2021
DOI: 10.1021/acsapm.1c01073
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Printing of Polyimide Films Using Passive Material Focusing

Abstract: In electrospray printing, a high electric potential is used to atomize a liquid solution containing the print material into a spray of charged microdroplets. Rapid solvent evaporation from the droplets renders a spray of charged dry particles that are directed onto a target substrate to print a film. Here, we report on electrospray printing of polyimide, an important polymer in electronics manufacturing, aerospace, and environmental applications. Using a passive electrostatic funnel to focus the print material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…The conductive FTO film is connected to a grounded aluminum base plate using copper tape. Under the influence of a strong electric field, the highly charged particles are directed to grounded surfaces. , The SU-8 photoresist acts as a surface energy pattern to modulate the wetting properties of the substrate, which defines the contact line (and, consequently, the interface geometry) of the target droplet. Additionally, SU-8 is a cross-linked polymer and an excellent electrical insulator.…”
Section: Resultsmentioning
confidence: 99%
“…The conductive FTO film is connected to a grounded aluminum base plate using copper tape. Under the influence of a strong electric field, the highly charged particles are directed to grounded surfaces. , The SU-8 photoresist acts as a surface energy pattern to modulate the wetting properties of the substrate, which defines the contact line (and, consequently, the interface geometry) of the target droplet. Additionally, SU-8 is a cross-linked polymer and an excellent electrical insulator.…”
Section: Resultsmentioning
confidence: 99%
“…The volatility of the carrier solvent, along with the electrospray and environmental conditions, governs the extent of solvent evaporation from the emitted droplets. In many cases (e.g., when using a highly volatile solvent), the solvent evaporates very quickly, resulting in dry (solvent-free) particles or aggregates of material delivered to the target surface. , However, if the solvent does not completely evaporate, the residual is delivered to the target along with the material and dramatically alters the deposited film morphology and microstructure. ,,, We define these two regimes as dry (solvent-free) and partially wet ESD, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al and Kovacevich et al have shown how electrosprays can be used to deposit polymer surface coatings on complex shapes and 3D-printed lattice structures. , Additionally, conformal coatings can be delivered to micro-scale geometries, such as biological stents . Unlike other deposition techniques, ESD films and coatings are self-limiting and grow nonlinearly due to charge accumulation in the growing film. , This is beneficial for providing uniform film coverage, especially for conformal coatings on intricate surface geometries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the only report of deposition efficiency in near-field templates comes from recent work of Kingsley et al, where they showed that for a still macroscopic (3 mm thick) insulating mask, the deposition efficiency using a SLED compatible material was reported to be less than 5%. 25 All additional material ostensibly found other grounded targets in their spray chamber. Angkawinitwong et al experimented with the coating of microneedle arrays (MNAs).…”
Section: Introductionmentioning
confidence: 99%